Interleukin‐13 immune gene therapy prevents CNS inflammation and demyelination via alternative activation of microglia and macrophages. Issue 12 (29th September 2016) - Guglielmetti, Caroline; Le Blon, Debbie; Santermans, Eva; Salas‐Perdomo, Angelica; Daans, Jasmijn; De Vocht, Nathalie; Shah, Disha; Hoornaert, Chloé; Praet, Jelle; Peerlings, Jurgen; Kara, Firat; Bigot, Christian; et al.
Abstract : Detrimental inflammatory responses in the central nervous system are a hallmark of various brain injuries and diseases. With this study we provide evidence that lentiviral vector‐mediated expression of the immune‐modulating cytokine interleukin 13 (IL‐13) induces an alternative activation program in both microglia and macrophages conferring protection against severe oligodendrocyte loss and demyelination in the cuprizone mouse model for multiple sclerosis (MS). First, IL‐13 mediated modulation of cuprizone induced lesions was monitored using T2 ‐weighted magnetic resonance imaging and magnetization transfer imaging, and further correlated with quantitative histological analyses for inflammatory cell influx, oligodendrocyte death, and demyelination. Second, following IL‐13 immune gene therapy in cuprizone‐treated eGFP + bone marrow chimeric mice, we provide evidence that IL‐13 directs the polarization of both brain‐resident microglia and infiltrating macrophages towards an alternatively activated phenotype, thereby promoting the conversion of a pro‐inflammatory environment toward an anti‐inflammatory environment, as further evidenced by gene expression analyses. Finally, we show that IL‐13 immune gene therapy is also able to limit lesion severity in a pre‐existing inflammatory environment. In conclusion, these results highlight the potential of IL‐13 to modulate microglia/macrophage responses and to improve disease outcome in a mouse model for MS. GLIA 2016;64:2181–2200 Main Points: Magnetic resonance imaging provides means to evaluate response to IL‐13 therapy. IL‐13 immune gene therapy protects against cuprizone‐induced demyelination. IL‐13 immune gene therapy induces alternative activation of microglia and macrophages.